2017
DOI: 10.1111/xen.12315
|View full text |Cite
|
Sign up to set email alerts
|

Level of acceptance of islet cell and kidney xenotransplants by personnel of hospitals with and without experience in clinical xenotransplantation

Abstract: Background: Recently, significant progress in both safety and efficacy has been achieved in the field of xenotransplantation, as exemplified by results from the first clinical trials of porcine islet transplantation. It would be of interest to learn whether the attitude of the clinical staff involved in such trials changes as the trials are carried out in their own hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…[3][4][5][6][7] Public opinion surveys have found that, in general, the perception of and willingness to consider XTx are favourable [8][9][10][11][12] , although the influence of religious beliefs was less straightforward. 8,[10][11][12] While theological discussions have suggested no specific prohibition from Abrahamic theological traditions (ie Jewish, Christian, and Muslim), [3][4][5][6][7] a review of public opinion survey responses related to the role of religious beliefs in the decision to consider a XTx was more complex. 8,[10][11][12] One recent study suggested that it was the amount of detailed information and procedure results that would have the greatest influence on religious acceptance of the procedure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7] Public opinion surveys have found that, in general, the perception of and willingness to consider XTx are favourable [8][9][10][11][12] , although the influence of religious beliefs was less straightforward. 8,[10][11][12] While theological discussions have suggested no specific prohibition from Abrahamic theological traditions (ie Jewish, Christian, and Muslim), [3][4][5][6][7] a review of public opinion survey responses related to the role of religious beliefs in the decision to consider a XTx was more complex. 8,[10][11][12] One recent study suggested that it was the amount of detailed information and procedure results that would have the greatest influence on religious acceptance of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12] While theological discussions have suggested no specific prohibition from Abrahamic theological traditions (ie Jewish, Christian, and Muslim), [3][4][5][6][7] a review of public opinion survey responses related to the role of religious beliefs in the decision to consider a XTx was more complex. 8,[10][11][12] One recent study suggested that it was the amount of detailed information and procedure results that would have the greatest influence on religious acceptance of the procedure. 12 Given the reality of future clinical trials, it is important to explore how various religious traditions might view XTx as a therapy, to better understand their theological views how each might address the importance of human health, and the use of pigs to bring health to others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of human islet allotransplantations that include need of multiple donor pancreases for single recipient infusion place further strain on an already restricted pancreas donor supply . Islet xenotransplantation, which involves the use of non‐human xenogeneic pancreatic islets donors, has shown promising results in both animal studies and clinical trials over the past three decades . Given the limited availability of human allograft donor supply and the recent breakthrough human clinical trials in the field of islet xenotransplantation, xenografts show potential to be a promising treatment for T1DM …”
Section: Introductionmentioning
confidence: 99%
“…As initial clinical trials draw closer, ethics [79], acceptance of xenotransplantation by hospital personnel [80], and by the general population with different cultural and religious backgrounds [8183], are topics of importance. Schuurman has recently comprehensively reviewed regulatory aspects of xenotransplantation in Europe and in the United States in his seminal papers [8485].…”
Section: Introductionmentioning
confidence: 99%